Hubungan Antara IMT, Aktivitas Fisik, Kebugaran Jasmani, dengan Prestasi Belajar Siswa Kelas X SMKN 2 Malang - Adopan Turnip, Frisko Lukas; Winarno, M.E (Ilmu Olahraga, 2024)
Learning achievement is the responsibility of teachers and the government, therefore everything that can encourage learning achievement must be considered and improved. Physical activity, BMI, physical fitness are several factors that influence learning achievement. The aim of this research is to determine the level of relationship between physical activity, BMI, and fitness and the learning achievement of class X students at SMKN 2 Malang. The research method used is a survey research method with a correlational research type. To determine the sample size, the researcher used the Slovin formula with an error rate of 10% with a class X student population of 656 students, so the sample size was 89 students. Because class X students are divided into 19 classes and so that each class has the same opportunities, the author uses the Proportional Random Sampling technique. IPAQ-SF to measure physical activity, IMT/U to measure BMI, and TKSI to measure physical fitness. The research results showed that physical activity was not significantly related to learning achievement with a P-Value of 0.809 > 0.05. BMI is not significantly related to learning achievement with P-Value 0.194 > 0.05. Physical fitness does not have a significant relationship with learning achievement, P-Value 0.893 > 0.05